Memórias da educação sexual: relatos de educadoras sobre a infância e adolescência - Spaziani, Raquel Baptista [UNESP]; Pereira, Patricia Cristine [UNESP]; Maia, Ana Cláudia Bortolozzi [UNESP] (My University, 2014)
Many educators have a history of sexual education characterized by sexual repression. Considering that the way people deal with their own sexuality may be related to the way they will approach the theme in the classroom, it is necessary to work with their sexual reeducation. Therefore, the present study aimed to investigate educators´s memory about childhood and adolescence sex education. For this purpose, eight educators wrote a redaction about his memories of family and school sex education. As a result, it could be seen that most of the participants described that their sexual education by family have been omissive and understanding the school was the place where they learned about the topic in biology classes and in informal conversations.

Muitos/as educadores/as possuem uma história de educação sexual caracterizada pela repressão sexual. Tendo em vista que a forma com que se lida com a própria sexualidade pode estar relacionada à maneira como irá se abordar o tema em sala de aula, faz-se necessário um trabalho de reeducação sexual com estes/as profissionais. Assim, o presente estudo teve como objetivo investigar as memórias de educadoras sobre a educação sexual que tiveram na infância e adolescência. Para isso, oito educadoras escreveram uma redação sobre as suas memórias da educação sexual familiar e escolar. Como resultado, pôde-se perceber que a maior parte das participantes descreveu uma educação sexual familiar omissa, compreendendo a escola como o local em que aprenderam sobre o tema, nas aulas de biologia e em conversas informais.
Sex education memories: reports of educators about childhood and adolescence
Keywords: Memories; Sexual education; Educators; Memórias; Educação sexual; Educadoras